2022
DOI: 10.7759/cureus.26533
|View full text |Cite
|
Sign up to set email alerts
|

Transfacet Oblique Lateral Lumbar Interbody Fusion: Technical Description and Early Results

Abstract: The oblique lateral lumbar interbody fusion (OLLIF) is a relatively new method of lumbar interbody fusion (LIF) that utilizes a trans-Kambin approach to the disc space. The OLLIF can be performed from T12-S1 in the majority of cases but is occasionally obstructed at the L5-S1 level by osteophytes, an overgrown facet joint and/or prominent sacral ala. Transfacet OLLIF (TF-OLLIF) is a novel method for LIF in which the disc space is accessed by drilling through hypertrophic facets with an OLLIF approach. We provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…38 It has also been reported that making 3 or more attempted passes through the Kambin triangle during a TLIF can increase the rate of nerve root irritation. 39 For this reason, the transfacet approach was introduced as an alternative option for patients who require larger cage dimensions or have anatomy which makes accessing the disk space through the other pathways more risky. First described by Khalifeh et al, 23 the proposed transfacet approach was a modification to the standard minimally invasive TLIF for the treatment of lumbar degenerative diseases and low-grade spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…38 It has also been reported that making 3 or more attempted passes through the Kambin triangle during a TLIF can increase the rate of nerve root irritation. 39 For this reason, the transfacet approach was introduced as an alternative option for patients who require larger cage dimensions or have anatomy which makes accessing the disk space through the other pathways more risky. First described by Khalifeh et al, 23 the proposed transfacet approach was a modification to the standard minimally invasive TLIF for the treatment of lumbar degenerative diseases and low-grade spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though multiple studies have demonstrated the necessity of pre-operatively measuring these corridors in order to define the safest trajectory for each patient’s specific spinal anatomy, a surgeon must also be prepared to alter their operative course if those corridors will not provide enough room for a successful interbody fusion [ 12 , 13 ]. For that reason, other minimally invasive approaches, such as the relatively novel transfacet approach, have begun to gain popularity as alternatives routes to the disc space since they provide better working areas for endplate preparation and larger cage dimensions [ 14 , 15 ]. Having said this, it is difficult to compare the relative areas and trajectories of each approach from only examining pre-operative 2D images like CT and MRI alone.…”
Section: Introductionmentioning
confidence: 99%